The ReInforcement of adherence via self-monitoring app orchestrating biosignals and medication of RivaroXaban in patients with atrial fibrillation and co-morbidities: a study protocol for a randomized controlled trial (RIVOX-AF) - Yoon, Minjae; Park, Jin Joo; Hur, Taeho; Hua, Cam-Hao; Shim, Chi Young; Yoo, Byung-Su; Cho, Hyun-Jai; Lee, Seonhwa; Kim, Hyue Mee; Kim, Ji-Hyun; Lee, Sungyoung; Choi, Dong-Ju (Frontiers in Cardiovascular Medicine, 2023)
Background: Due to the relatively short half-life of non-vitamin K antagonist oral anticoagulants (NOAC), consistent drug adherence is crucial to maintain the effect of anticoagulation for stroke prevention in patients with atrial fibrillation (AF). Considering the low adherence to NOAC in practice, we developed a mobile health platform that provides an alert for drug intake, visual confirmation of drug administration, and a list of medication intake history. This study aimed to evaluate whether this smartphone app-based intervention would increase drug adherence compared to usual care in patients with AF requiring NOAC in a large population. Methods: This prospective, randomized, open-label, multicenter trial (RIVOX-AF study) will include a total of 1,042 patients (521 patients in the intervention group and 521 patients in the control group) from 13 tertiary hospitals in South Korea. Patients with AF aged ≥19 years with one or more comorbidities, including heart failure, myocardial infarction, stable angina, hypertension, or diabetes mellitus, will be included in this study. Eligible participants will then be randomly assigned to either the intervention group (MEDI-app) or the conventional treatment group in a 1:1 ratio using a web-based central randomization service. Patients in the intervention group will use a smartphone app that includes an alarm for drug intake, visual confirmation of drug administration through a camera check, and presentation of the list of medication intake history. The primary endpoint is adherence to rivaroxaban by pill count measurements at 12 and 24 weeks. The key secondary endpoints are clinical composite endpoints, including stroke, systemic embolic event, major bleeding requiring hospitalization or transfusion, or death during the 24 weeks of follow-up. Discussion: This randomized controlled trial will investigate the feasibility and efficacy of smartphone apps and mobile health platforms in improving adherence to NOAC.